ASPEK HUKUM PERLINDUNGAN PEREMPUAN DAN ANAK DALAM NIKAH SIRI - Rihlatul Khoiriyah (Sawwa: Jurnal Studi Gender, 2017)
Marriage that is not registered to the office of religious affairs (KUA) is considered as Siri marriage. It often occurs in the society while invites pros and cons among them.  The perpetrators usually have different motivations to commit this kind of marriage. Unfortunately, marriage law does not set unequivocally about the legal status of Siri marriage. But it emphasizes the importance of registered marriage as a legal event. The registration of marriage has significance to the various events that are resulted from the marriage: the administration of population and the guarantee of civil rights for the concerned parties. The occurrence of Siri marriage will cause problems for the perpetrators and their families, both legal and social problems. Nevertheless there are positive and negative values in this marriage. So, the aspects of maslahat and madlarat should be considered in order to realize the legitimate purpose of marriage._________________________________________________________Perkawinan yang tidak dicatatkan di Kantor Urusan Agama (KUA) dikenal sebagai kawin siri. Perkawinan ini sering terjadi dalam masyarakat dan mengundang pro dan kontra diantara mereka. Pelaku kawin siri mempunyai berbagai ragam motivasi yang berbeda satu dengan lainnya. Sayangnya, hukum perkawinan tidak mengatur secara tegas tentang status hukum kawin siri. Hukum perkawinan hanya menekankan arti pentingnya pencatatan perkawinan sebagai sebuah peristiwa hukum. Pencatatan perkawinan ini mempunyai arti penting terhadap berbagai peristiwa yang ditimbulkan sebagai akibat adanya perkawinan baik administrasi kependudukan maupun jaminan hak-hak keperdataan bagi para pihak yang berkepentingan. Terjadinya kawin siri akan menimbulkan problematika bagi para pelakunya dan keluarganya, baik problematika hukum maupun problematika sosial. Meskipun demikian terdapat nilai positif dan negatif pada kawin siri tersebut. Oleh karena itu harus dipertimbangkan aspek maslahat dan madlarat agar perkawinan siri tersebut sesuai dengan tujuan disyari’atkannya perkawinan.